PEMERTAHANAN BAHASA DAERAH MELALUI PEMBELAJARAN DAN KEGIATAN DI SEKOLAH - Widianto, Eko (Universitas Muria Kudus, 2018)
Language maintenance and shift are like two sides of a coin. Language maintenance arises from a language shift in a language society. Therefore, both are present simultaneously. Language shifts usually occur in regional languages such as Java, Sundanese, Bugis, etc. Language maintenance can be done through education. Education becomes an important element in preparing future generations. This paper describes a form of local language maintenance through education, which is a form of local language maintenance through learning, community or extracurricular, and as a mandatory communication tool on a certain day. In addition, it is also described as a function of local language maintenance through education.